Fibronectin promotes cell proliferation and invasion through mTOR signaling pathway activation in gallbladder cancer. Issue 2 (1st May 2015) - Cao, Yang; Liu, Xiyong; Lu, Wei; Chen, Yuanyuan; Wu, Xiangsong; Li, Maolan; Wang, Xu-an; Zhang, Fei; Jiang, Lin; Zhang, Yijian; Hu, Yunping; Xiang, Shanshan; et al.
Highlights FN is overexpressed in GBC tissues and is associated with a worse prognosis in GBC patients. Exogenous FN treatment promotes the proliferation and invasiveness of GBC cells. The Akt/mTOR/4E-BP1 signaling pathway is critically involved in FN-induced GBC cell proliferation and invasion.